Thermal Comfort in Naturally Ventilated Classroom: A Literature Review - Mohamad Zamri, Ernisuhani; Ismail, Asmat; Md Ajis, Azizah (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
A phenomenon of global climate change and global warming led to an increase of study on indoor thermal comfort as it causes an increase in air temperature in both outdoor and indoor environments. Thermal comfort of indoor condition had a significant impact on occupants' performance, especially in the educational building. The impact is more crucial in a natural ventilated building as it is influenced by both outdoor and indoor condition. This paper presents an overview of a study on thermal comfort over the past ten years in the classroom that use the passive ventilation system. The study is divided into two sections; the first reviews the variables that are measured to determine thermal comfort and the second section reviews the other factors that could influence the thermal comfort. The factors that have been reviewed include climatic condition, design of ventilation system of the building, building envelope design and occupants behaviour that had influence the thermal comfort in the building, hence influenced the occupants' performance. Most of the studies had found that the occupants were dissatisfied with the indoor environment and the results of the studies found that thermal comfort is not in the comfort range, as stated in the standards. The ventilation factor has been highlighted in most studies to be the crucial factor that influences the indoor environment and thus influence the thermal comfort of the building.